Pruning management of ‘Marselan’ grapevines in the Serra do Sudeste region, in Southern Brazil - Medeiros dos Santos, Cibele; Rodrigues Viera, Carla Thais; Braga de Andrade, Suélen; Roberto Martins, Carlos (Comunicata Scientiae, 2020)
The agronomical behavior of the ‘Marselan’ grapevine, indicated for the production of high-quality fine wines, is related to the management of the vineyard and the edaphoclimatic conditions of the cultivation region. This work aimed to evaluate the vegetative, productive, and qualitative behavior of ‘Marselan’ grapevines subjected to the Spur Pruning and Double Guyot pruning systems, cultivated in a municipality belonging to the Serra do Sudeste region, RS state, Brazil. The ‘Marselan’ grapevines were conducted in a vertical shoot positioning training system over a ‘Paulsen 1103’ rootstock, in a commercial vineyard located in Encruzilhada do Sul, RS, Brazil. During the 2016/2017 and 2017/2018 cropping seasons the vegetative vigor, the mass of pruned shoots, Ravaz Index, production, and chemical-physical composition of the must were evaluated. The double Guyot pruning system in the ‘Marselan’ grapevines induced a lower plant vigor, promoted an increase in the number of bunches per plant, bunch mass, production, and yield. The pruning type interferes with the vigor and yield of the ‘Marselan’ grapes without altering must quality. In the management of the cv. ‘Marselan’ in the Serra do Sudeste region, Brazil, the double Guyot pruning system is the most indicated.